2022
DOI: 10.1024/0300-9831/a000727
|View full text |Cite
|
Sign up to set email alerts
|

Higher intakes of dietary caffeine are associated with 25-hydroxyvitamin D deficiency

Abstract: Abstract. Low serum 25-hydroxyvitamin D [25(OH)D] levels remain a challenge worldwide. While some in vitro studies show a caffeine-induced decrease in vitamin D receptor expression, there is a paucity of research to define the extent of caffeine intake on 25(OH)D levels. Therefore, we aimed to associate dietary caffeine intake with 25(OH)D deficiency through a recognized dataset. Using data collected from the 2005–2006 National Health and Nutrition Examination Survey (NHANES), 25(OH)D levels and dietary caffei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Several other studies reported inconsistent findings regarding vitamin D levels and caffeine intake (45)(46)(47). Although there are contradictions in reports of coffee consumption and vitamin D levels, the results of our study are in line with the two biggest studies performed in healthy adult individuals (42,43).…”
Section: Inverse Associations Between Food Groups and Vitamin D Level...supporting
confidence: 87%
See 1 more Smart Citation
“…Several other studies reported inconsistent findings regarding vitamin D levels and caffeine intake (45)(46)(47). Although there are contradictions in reports of coffee consumption and vitamin D levels, the results of our study are in line with the two biggest studies performed in healthy adult individuals (42,43).…”
Section: Inverse Associations Between Food Groups and Vitamin D Level...supporting
confidence: 87%
“…Regarding association of coffee intake and vitamin D levels, two large-scale observational studies reported negative association between vitamin D levels and coffee intake (42,43). Another study of 741 premenopausal women, which is more similar to ours with respect to the age and the sex of participants, found statistically significant association between higher intake of caffeine containing cola drinks, assessed through FFQ, and decreased vitamin D levels (44).…”
Section: Inverse Associations Between Food Groups and Vitamin D Level...supporting
confidence: 78%
“…Low serum 25(OH)D levels continue to be a problem worldwide. While some in vitro studies show a caffeine-induced decrease in vitamin D receptor expression, more research is needed to determine the extent of caffeine consumption and its effects on 25(OH)D levels [ 13 ]. This study has found no significant differences between vitamin D levels of the women with different amounts of milk consumption in both groups.…”
Section: Discussionmentioning
confidence: 99%